Research Focused on the Development of Technical Literacy of Elementary School Students - BEISETZER, PETER (Journal of Education, Technology and Computer Science, 2023)
The article describes a strategic approach to the development of technical literacy of elementary school students from the point of view of research activities. The research activity is concretized for the development of graphic, spatial imagination, which is assumed by the activities related to the understanding of the text. Research aimed at determining the degree of correlation between reading an educational text with comprehension and geometric, spatial imagination will contribute to the evaluation of the issue.